Analysis of Beginning Reading Skills of 2nd Grade Students at Integrated Islamic Elementary School Tahfidzul Quran An-Nahl Mataram - Thufail Mujaddid Al-Qoyyim; Siti Maulidiya Nabila; Muhaini Muhaini; Siti Hajariah; Affan Affan; Aida Atika Suri; Buntana Buntana (MANDALIKA : Journal of Social Science, 2024)
Reading proficiency is a foundational skill in elementary education, significantly influencing students' academic success and personal development. This study investigates the initial reading abilities of 2nd-grade students at Integrated Islamic Elementary School Tahfidzul Quran An-Nahl, an institution that combines general and religious education. The research identifies key areas for improvement and evaluates the effectiveness of current teaching methods. Using a descriptive quantitative approach, the study assesses three main indicators: pronunciation accuracy, reading fluency, and voice clarity. Data were collected through reading tests and teacher questionnaires. Results reveal significant challenges, with most students rated as "Poor" or "Fair." Factors such as inconsistent phonetic teaching, insufficient reading practice, and unsupportive learning environments contribute to these difficulties. Recommendations include enhancing phonetic instruction, increasing reading practice, and fostering a supportive reading environment. This study provides insights for developing effective literacy programs in similar educational contexts, aiming for holistic improvements in students' reading skills